2013
DOI: 10.1111/jabr.12009
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Human Frontal Cortex Under Noxious Thermal Stimulation Over the Temporomandibular Joint Using Functional Near Infrared Spectroscopy

Abstract: Functional near infrared spectroscopy (fNIRS) was used to explore hemodynamic responses in the human frontal cortex to noxious thermal stimulation over the right temporomandibular joint (TMJ). fNIRS experiments were performed on nine healthy volunteers under both low‐pain stimulation (LPS) and high‐pain stimulation (HPS), using a temperature‐controlled thermal stimulator. By analyzing the temporal profiles of changes in oxy‐hemoglobin concentration (HbO) using cluster‐based statistical tests, several regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…First, Becerra et al found qualitative correlations between thermally-induced pain and temporal characteristics of hemodynamic responses (HbO) in the somatosensory cortex of a group of human subjects. 26 In the recent 2 to 3 years, a few other fNIRS-based pain studies (including ours) have reported investigations of (1) prefrontal hemodynamic responses to mechanically induced low back pain 27 and thermally stimulated temporomandibular joint (TMJ) pain, 28 as well as (2) somatosensory hemodynamic responses to noxious electrical stimulation of the thumb. 29 While these studies showed detectable and quantifiable changes of HbO by fNIRS in the human PFC induced by pain stimulation, it is unknown whether such pain-induced HbO signals are detected consistently within similar PFC areas in spite of pain-originating locations (i.e., from different body sites) or pain-inducing types (such as thermal versus mechanical pains).…”
Section: Motivation Of This Studymentioning
confidence: 88%
“…First, Becerra et al found qualitative correlations between thermally-induced pain and temporal characteristics of hemodynamic responses (HbO) in the somatosensory cortex of a group of human subjects. 26 In the recent 2 to 3 years, a few other fNIRS-based pain studies (including ours) have reported investigations of (1) prefrontal hemodynamic responses to mechanically induced low back pain 27 and thermally stimulated temporomandibular joint (TMJ) pain, 28 as well as (2) somatosensory hemodynamic responses to noxious electrical stimulation of the thumb. 29 While these studies showed detectable and quantifiable changes of HbO by fNIRS in the human PFC induced by pain stimulation, it is unknown whether such pain-induced HbO signals are detected consistently within similar PFC areas in spite of pain-originating locations (i.e., from different body sites) or pain-inducing types (such as thermal versus mechanical pains).…”
Section: Motivation Of This Studymentioning
confidence: 88%
“…1 Similar relation has been reported between subjects' self-report and functional near-infrared spectroscopy (fNIRS) parameters. [2][3][4][5][6][7][8] For example, Lee et al 4 reported that as the intensity of the noxious pressure stimuli increases, the HbO 2 in the frontal cortex increases as well, consistent with an increase in the perceived pain.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies using functional magnetic resonance imaging (fMRI) have confirmed that BOLD signals, originating from regional deoxy-hemoglobin concentration changes, are altered due to thermal pain and can be used as biomarkers to objectively assess pain [ 5 , 6 ]. Similarly, several human studies using near infrared spectroscopy have demonstrated that thermal or electrical stimulations induce changes of hemoglobin concentrations at different brain regions [ 7 , 8 , 9 ]. However, many important physiological questions related to pain processing at different neurological sites cannot be answered using a non-invasive approach in human subjects.…”
Section: Introductionmentioning
confidence: 99%